101 ready-to-use Excel macros - Alexander, Michael, 1972-; Walkenbach, John. (Hoboken, N.J. : John Wiley & Sons, 2012)
Annotation Save time and be more productive with this helpful guide to Excel macros!While most books about Excel macros offer only minor examples, usually aimed at illustrating a particular topic, this invaluable resource provides you with the tools needed to efficiently and effectively program Excel macros immediately. Step-by-step instructions show you how to create VBA macros and explain how to customize your applications to look and work exactly as you want them to. By the end of the book, you will understand how each featured macro works, be able to reuse the macros included in the book and online, and modify the macro for personal use. Shows you how to solve common problems with the featured macros, even if you lack extensive programming knowledge.
pt. 1. Getting started with Excel macros -- pt. 2. Working with workbooks -- pt. 3. Automating worksheet tasks with macros -- pt. 4. Selecting and modifying ranges -- pt. 5. Working with data -- pt. 6. Working with PivotTables -- pt. 7. Manipulating charts with macros -- pt. 8. E-mailing from Excel -- pt. 9. Integrating Excel and other office applications.
Includes index.
Keywords: Microsoft Excel (Computer file); Microsoft Excel (Computer file); Domain-specific programming languages; Macro instructions (Electronic computers); Electronic spreadsheets; Computer science; COMPUTERS -- Desktop Applications -- Spreadsheets; Domain-specific programming languages; Electronic spreadsheets; Macro instructions (Electronic computers); Electronic books; Electronic books; Electronic books